VHL Syndrome with Diabetes Mellitus, and Pulmonary and ThyroidNodules (Journal of Kidney Cancer, 2025)
Von Hippel–Lindau (VHL) syndrome is an autosomal dominant hereditary tumor syndrome caused by mutations in the VHL gene. It is characterizedby the occurrence of tumors in multiple organs. Pancreatic involvement in VHL syndrome can present as pancreatic cysts or neuroendocrinetumors, which may interfere with both pancreatic exocrine and endocrine pancreatic functions. To our knowledge, no patients with VHLsyndrome complicated by diabetes mellitus, pulmonary nodules, and thyroid nodules are reported in the literature. This study aims to explore thepathogenesis of diabetes, pulmonary nodules, and thyroid nodules in VHL syndrome through the analysis of a patient with VHL syndrome andto review relevant literature.